Models Of Economic Psychology And Economic Behavior - Son of Omonov Sherali Ibrahim (Euro Asian Journal Publishing, 2024)
The article outlines theories that the study of models of economic psychology and economic behavior, economic psychology or the psychological aspects of the economy is an area of promising scientific research.
Keywords: economics; behavior; government; model